DIGITAL GOVERNANCE PADA LEMBAGA FILANTROPI ISLAM: ANALISIS TATA KELOLA ORGANISASI DALAM PENGELOLAAN ZAKAT DAN SEDEKAH BERBASIS TEKNOLOGI - Elok Maziyyah Zulaicho (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital transformation has encouraged Islamic philanthropic institutions to adopt digital governance in order to improve organizational effectiveness, transparency, and accountability. This study aims to analyze the implementation of digital governance at Rumah Zakat Kediri in optimizing the collection and distribution of zakat, infaq, sadaqah, and other Islamic social funds. This research employed a qualitative approach using a case study design. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings reveal that digital governance has been implemented through technology-based strategic planning, well-structured organizational management, the utilization of digital platforms for fundraising and distribution services, and strengthened transparency and accountability supported by digital information systems. These practices have improved operational efficiency, accelerated services for donors and beneficiaries, and enhanced public trust in the institution. Nevertheless, several challenges remain, including technological infrastructure, data security, human resource competencies, and community digital literacy. This study concludes that digital governance plays a significant role in establishing professional, adaptive, transparent, and sustainable governance within Islamic philanthropic institutions in the era of digital transformation.